Organic carbon in Mollisols of the world − A review - Labaz, Beata; Hartemink, Alfred E.; Zhang, Yakun; Stevenson, Annalisa; Kabała, Cezary (Geoderma, 2024)
•Globally, the mean thickness of the A horizon in Mollisols is 50 cm.•The highest SOC con. and pools are in Mollisols from Eastern Europe and Asia.•Mollisols under grassland have the largest SOC pools.•Soil moisture and temperature regimes determine SOC storage in Mollisols.•The important factors on SOC storage are soil texture, land use, and soil temperature regime. Mollisols represent 29 % of agricultural land and they are considered to be one of the most fertile soils in the world. Here, we compare soil organic carbon (SOC) concentrations and pools of Mollisols for the globe, the USA and Poland, and review how differences are caused by climate, land use, and key environmental factors. Globally, the mean thickness of the A horizon in Mollisols is 50 cm. At 0–30 cm the mean SOC concentration is 2.3 %, SOC pool is 84 t ha−1, and clay content calculated at 0–50 cm soil depth is 21 %. Mollisols in the USA have an A horizon thickness of 36 cm and have a mean clay content of 27 % (0–50 cm). SOC concentrations are 2.0 and 1.7 % and SOC pools are 85 and 116 t ha−1 at 0–30 and 0–50 cm soil depth, respectively. Mollisols in Poland have SOC concentrations of 1.8 and 1.5 % at 0–30 and 0–50 cm soil depth, respectively, and lower clay content (17 %) at 0–50 cm depth. The SOC pool at 0–30 cm depth is 74 t ha−1 whereas it is 106 t ha−1 at 0–50 cm. At the global scale, the highest SOC concentrations and pools are in Mollisols from Eastern Europe (including Ukraine and Western Russia) and Asia, while the lowest SOC pools are found in Mollisols from South America. The Mollisols in Western and Central Europe and North America have similar SOC pools, although Mollisols in North America have higher SOC concentrations and lower A horizon thickness. Globally, the mean pH value of Mollisols is 7.1, and the pH is slightly lower in Mollisols of the USA (6.9 ± 0.9). The SOC concentrations and pools are strongly and positively correlated with clay content. Soil moisture and temperature regimes determine SOC concentration and pools in Mollisols, and higher SOC concentrations and pools are in Mollisols with frigid and frigid-cryic soil temperature regimes as well as aquic, xeric, and aridic soil moisture regimes. Mollisols under grassland have the largest SOC pools compared to those cultivated or under forest. The important environmental factors on SOC concentrations and pools in Mollisols worldwide are soil texture, land use, and soil temperature regime.